Latest progress on 3.5 GHz 5G NR trial - Guangyi LIU; Qixing WANG; Jianjun LIU; Fei WANG; Yi ZHENG (Tongxin xuebao)
The 5thgeneration mobile system (5G) was designed to fulfill the mobile market requirements for higher data rate,lower latency and higher connection density beyond 2020.3.5 GHz spectrum was a typical band for 5G deployment and could be a global band for 5G development.The performance of 3.5 GHz 5G would be very meaningful as a reference for global operators.Based on the first release of 5G specification frozen in June 2018 by 3rdgeneration partner project (3GPP),field trials of 5G network in typical urban area were conducted to validate the peak data rate,cell throughput and latency of 5G network.The trial results show that 5G NR system can achieved 1 Gbit/s peak data rate and 4 ms latency of single direction.